The influence of household socio-economic profiles on the use of mangrove resources along the Benin coastline - Akoton, Tété Pérugine; Hountondji, Yvon Carmen; Sourou, Bienvenue Nawan; Tcheton, Sènankpon; Wedjangnon, Adigla Appolinaire; Houètchégnon, Towanou; Sogbossi, Sènadémi Erick; Salako, Kolawolé Valère; Ouinsavi, Christine Ajokè Ifètayo Nougbodé (Frontiers in Ocean Sustainability, 2025)
IntroductionThe mangrove ecosystems are crucial marine ecosystems, providing various ecological and economic benefits to local communities. This study aims to analyze the influence of household socio-economic profiles on mangrove ecosystems resources in Benin.MethodsBased on semi-structured interviews, 464 households were surveyed in 73 localities. The Specific Multiple Correspondence Analysis (spMCA) combined with Hierarchical Ascendant Classification (HAC) was used to analyze the socio-economics, demographics, and environmental data collected. The priority scores of the surveyed households were used to perform the influence of households to mangrove resources by coupling HAC to Principal Component Analysis (PCA).ResultsFive household categories (labeled CM1–CM5) were identified. They represent varying levels of vulnerability, access to resources, and modes of mangrove resource use. The household of CM1 are highly dependent on mangrove resources and distributed proportionally across the study sub-sectors whereas the CM5 household are the most vulnerable, located around the biosphere reserve, and facing land tenure insecurity, extreme poverty, and significant pressure on mangrove ecosystems. The household categories are strongly influenced by the dependency on biosphere reserve resources and sociolinguistic affiliation. The gender and education level play a secondary role on household categories structuring. Five groups of pressure factors on the mangroves were associated with the different household categories. Salt farming, wood cutting, and backfilling of waterways are predominant for CM1, CM2, CM3, and CM5. Land overexploitation, depletion of fishery resources, and climatic factors are the mainly determinants for CM4 and CM5. Land conflicts and declining agricultural yields are also mentioned by CM5.ConclusionThese results highlight the need for differentiated mangrove management strategies, tailored to the specific socio-economic characteristics of the households. Co-management, reforestation, and awareness-raising activities, represent strategic targets for sustainable conservation policies. Also, specific support measures, including the development of sustainable economic alternatives and improved access to basic services are needed. Taking this typology into account would improve the effectiveness and equity of environmental policies related to mangrove management.